FLOOD HYDROGRAPH PROJECTION BASED ON RAINFALL AND LAND COVER DATA (CASE STUDY OF DAYEUHKOLOT WATERSHED) - Eka Putra, Ronny
Dayeuhkolot, located 9 km from the center of Bandung or approximately 18 km from Soreang, is part of the sub-Citarum watershed that experiences floods every year. The causes of these floods involve natural factors such as high rainfall and human factors such as clogged or damaged drainage channels, improper land use, deforestation in the upstream area, and other contributing factors. These floods result in loss of life and damage to property. Population growth also contributes to increasing urbanization, reducing the area's ability to absorb water, and increasing the peak and volume of water during floods. Flood hydrograph projections are based on rainfall data from GSMaP and land cover data in this study. The flood hydrograph method used is the SCS curve number method. Flood events were analyzed from 12 occurrences with river discharge exceeding 300 m3/second from 2018 to 2022. Subsequently, a calibration and validation process was conducted using a trial and error approach with HEC - HMS software to obtain hydrological parameter values and ArcGIS to acquire land cover curve values. The next stage involves calibrating the values obtained from the HEC - HMS modeling by classifying land cover from 2018 to 2022. The predicted results and calibrated hydrological parameters are used as input for flood hydrograph projections in 2100. The Malaccha Method is utilized to predict land cover in 2100.